2017
DOI: 10.1038/s41598-017-01826-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Akt-independent mTORC1 and GSK3β signaling in sublethal NMDA-induced injury and the recovery of neuronal electrophysiology and survival

Abstract: Glutamate-induced excitotoxicity, mediated by overstimulation of N-methyl-D-aspartate (NMDA) receptors, is a mechanism that causes secondary damage to neurons. The early phase of injury causes loss of dendritic spines and changes to synaptic activity. The phosphatidylinositol-4,5-bisphosphate 3-kinase/Akt/ mammalian target of rapamycin (PI3K/Akt/mTOR) pathway has been implicated in the modulation and regulation of synaptic strength, activity, maturation, and axonal regeneration. The present study focuses on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 88 publications
0
13
1
1
Order By: Relevance
“…8, C and D). Akt-independent activation of mTORC1 is known (79,81). However, expression of constitutively active Myr Akt reversed the attenuation of S6 kinase phosphorylation induced by anti-miR-214 ( Fig.…”
Section: G-i)mentioning
confidence: 92%
“…8, C and D). Akt-independent activation of mTORC1 is known (79,81). However, expression of constitutively active Myr Akt reversed the attenuation of S6 kinase phosphorylation induced by anti-miR-214 ( Fig.…”
Section: G-i)mentioning
confidence: 92%
“…In synaptic potentiation, high-frequency spiking events involve the transient surge of postsynaptic Ca ++ current that is mediated by NMDAR-linked ionotropic neurotransmission (Xia et al, 1996; Coultrap and Bayer, 2012). In addition to the modulation of synaptic plasticity, the transient Ca ++ current also couples LTP to cellular regulation and gene expression (Xia et al, 1996; Li et al, 2001; Yao and Wu, 2001; Salter and Kalia, 2004; Yoshii and Constantine-Paton, 2007; Coultrap and Bayer, 2012; Stein et al, 2015; Takei et al, 2015; Sanderson et al, 2016; Wang et al, 2016; Swiatkowski et al, 2017). Ca ++ surge produced by NMDAR activates synaptic Ca ++ -Calmodulin-dependent kinase 2 (CaMKII) by facilitating autophosphorylation at T286/287 sites of the 9α/3β components of the holoenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has shown that rapamycin, a tool for the study of the Akt/mTOR signaling pathway, can effectively reduce the mechanical sensitivity of rats with chronic inflammatory pain. [ 26 ] After pretreatment with rapamycin, the late maintenance of long-term potentiation and long-term memory formation in the hippocampus were blocked, and the hyperalgesia induced by formalin was reduced; moreover, the excitability of spinal dorsal horn neurons was also significantly decreased. [ 27 28 ] To better understand, the effect of rapamycin on neuropathic pain, we applied rapamycin to stavudine-treated mice to further explore the role of rapamycin in hyperthermia and mechanical pain abnormalities.…”
Section: Discussionmentioning
confidence: 99%